The association of left atrial mechanics with left ventricular morphology in patients with hypertrophic cardiomyopathy: A cardiac magnetic resonance study - Güler, Arda; Topel, Çağdaş; Şahin, Ahmet Anıl; Aydın, Sinem; Güler, Ekrem; Memiç Sancar, Kadriye; Türkvatan Cansever, Aysel; Güler, Gamze Babur; Ertürk, Mehmet (International Scientific Information, Inc., 2023)
Purpose: Hypertrophic cardiomyopathy (HCM) is related with structural and pathologic changes in the left atrium (LA) and left ventricle (LV). The aim of this study was to explore the association between LA mechanics and LV charac-teristics in patients with HCM using cardiac magnetic resonance feature tracking (CMR-FT). Material and methods: A total of 76 patients with HCM and 26 healthy controls were included in the study. The pa-rameters including the extent of LV late gadolinium enhancement (LGE-%) and the LV early diastolic longitudinal strain rate (edLSR) were assessed for LV. LA conduit, booster, and reservoir functions were assessed by LA fractional volumes and strain analyses using CMR-FT. HCM patients were classified as HCM patients without LGE, with mild LGE-% (0% < LGE-% >= 10%), and prominent LGE-% (10% < LGE-%).Results: HCM patients had worse LA functions compared with the controls (p < 0.05). The majority of LA functional indices were more impaired in HCM patients with regard to LGE. LA volumes were higher in HCM patients with prominent LGE-% compared with HCM patients with mild LGE-% (p < 0.05). However, only a minority of LA functional parameters differed between the 2 groups. LA strain parameters showed weak to modest correlations with LV LGE-% and LV edLSR.Conclusions: LV characteristics, to some extent, influence LA mechanics, but they might not be the only factor induc-ing LA dysfunction in patients with HCM.
Keywords: Cardiac Magnetic Resonance; Hypertrophic Cardiomyopathy; Left Atrium; Late Gadolinium Enhancement